Eichhornia crassipes biomass as a dietary supplement for Pterophyllum scalare (Schultze, 1823) - Lúcia Helena Sipaúba-Tavares; Juliane dos Santos Alves da Silva; João Batista Kochenborger Fernandes (Acta Scientiarum. Animal Sciences, 2019)
Current study evaluates the macrophyte biomass of water hyacinth, Eichhornia crassipes, in diet food to improve the growth and survival of angelfish, Pterophyllum scalare. The liquid (extract) and ground modes are employed. Specific growth rate, weight gain, feed intake and final body weight in basal diet and macrophyte extract biomass diets were similar (p > 0.05). Fish survival was high in all dietary treatments (> 90%), while survival percentage of 100% was reported in ground macrophyte biomass treatment. Ground macrophyte biomass may be included in the diet of P. scalare up to 5%. The inclusion of E. crassipes in the diet of P. scalare proved similar or better results than basal diet. The macrophyte proved to be a food strategy in angelfish diets that may be implemented in the species’s diet at 32% levels of crude protein. The latter, easily found in tropical regions, affects directly the species’s growth and survival rates.